Environmental Psychology for The 21st Century: The Challenge of Sustainable Development - Moser, Gabriel (Revista de Psicología, 2003)
With the millennium upon us, environmental psychology needs to take account of two variables which have, until now, been inadequately considered: intercultural differences and the temporal dimension of people - environment relations. The cultural factor cannot be ignored in western societies which are increasingly intercultural, and our relation to the built as well as the natural environment needs to be analysed in terms of temporality. This paper analyses the impact of intercultural factors and the time perspective on four levels of analysis the micro-environment, the proximate environment, urban environment and the global environment. To look at these four levels and at their interrelations is particularly important when we have to meet the sustainable development exigencies towards the individual’s well-being and quality of life, which are dependent on cultural specific needs.